Spatial and temporal analysis of changes in the glaciers of the Antarctic Peninsula - Silva, Aline Barbosa; Arigony-Neto, Jorge; Braun, Matthias; Espinoza, Jean Marcel Almeida; Costi, Juliana; Janã, Ricardo (Global and Planetary Change, 2020)
The Antarctic Peninsula shows considerable spatial variability concerning its glaciological characteristics. It has also been subjected to severe climate changes, with reported glaciological consequences. However, such changes did not occur uniformly across the region. The present study aimed to characterize the glaciers of the Antarctic Peninsula geomorphologically and identify the spatial patterns of changes in their frontal position, generating an inventory of these features that will be part of the Global Land Ice Measurements from Space project. The study comprised the period between 1991 and 2015. We used ASTER imagery and ASTER GDEM and RAMP DEM digital elevation models to map the limits of glacial drainage basins. Landsat TM and ETM + data and the Antarctic Digital Database were used in areas not covered by ASTER images. We applied a supervised classification method to the satellite images to generate a mask of ice-free areas. The inventory of glaciers resulted in the delimitation of 1906 drainage basins between latitudes 61°S and 73°S, corresponding to an area of 476,507.83 km2. Ice-free areas occupied 5363.38 km2 (1% of the total). Between 2001 and 2015, 1339.68 km2 of ice was lost, corresponding to 1093 glaciers, while the area covered by glacier advance was estimated in 91.34 km2, corresponding to 255 glaciers, and 240 oscillating glaciers (gaining and losing ice mass). Thirty-nine percent of glaciers showed a slight retreat, 21% marked retreat, and 9% advanced during the period studied. The 16 ice shelves comprised an area of 137,677.16 km2, from which only 128,436.08 km2 remained until 2015. Eleven ice shelves experienced retreat during the period studied. We identified spatiotemporal variability patterns of the glaciers using statistical analysis by implementing empirical orthogonal functions (EOF), in which the first two EOFs represented approximately 87% of the space-time variability pattern of the glaciers. The glaciers classified as outlet glaciers (61%) were identified as the most sensitive to change, especially regarding frontal retreat. The glacial catchments classified as calving and floating were the most sensitive considering any change both in advance and retreat of their frontal area.
CRIS-Team Scopus Importer:2019-11-22
Keywords: Calving glaciers; Empirical orthogonal functions; Geomorphological classification; Ice front retreat; Inventory of glaciers